1998
DOI: 10.1159/000018625
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin in Early Detection of Postoperative Complications

Abstract: Background: A prospective clinical study was performed to assess the accuracy of procalcitonin in 70 patients with elective colorectal or aortal surgery and to compare it with inflammatory mediators. Also the early prediction of complications and the outcome of these patients was taken into account. Methods: Laboratory variables and cytokine determination were obtained preoperatively, on the day of operation and postoperatively on a daily basis from day 1 to 5, and on days 7 and 10 in the colorectal group and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
71
0
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(83 citation statements)
references
References 8 publications
6
71
0
5
Order By: Relevance
“…Reith et al 33 showed a marked increase in blood PCT, from 0·19 to I·2ltg/L, after uncomplicated surgery, whereas with complications the increase was from 0·36 to 6·9ltg/L. Meisner et «» showed that patients undergoing minor aseptic operations had increased plasma PCT in about one-third of cases, but seldom to levels above I j.tg/L.…”
Section: Procalcitonin As a Marker Of Infection Following Surgerymentioning
confidence: 98%
“…Reith et al 33 showed a marked increase in blood PCT, from 0·19 to I·2ltg/L, after uncomplicated surgery, whereas with complications the increase was from 0·36 to 6·9ltg/L. Meisner et «» showed that patients undergoing minor aseptic operations had increased plasma PCT in about one-third of cases, but seldom to levels above I j.tg/L.…”
Section: Procalcitonin As a Marker Of Infection Following Surgerymentioning
confidence: 98%
“…The only marker widely accepted in the clinical setting is procalcitonin. However, procalcitonin remains controversial for differentiation of SIRS/sepsis because it has been described to be elevated after major surgery, a common cause of SIRS without underlying infection (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Moreover, a higher concentration of PCT correlates with more severe trauma and a higher incidence of various complications, including sepsis [22]. In the postoperative period following elective colorectal or aortal surgery, PCT seems to be a valuable early predictive marker of infective complications when high postoperative levels are found [25]. Although the association between PCT and elective colorectal surgery has been widely investigated [25,26], the predictive role of PCT levels on the prognosis of sepsis in the elderly following emergency colorectal surgery has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%